Measuring quantity in ecosystem markets and ecosystem accounts - Stoneham, Gary; Beverly, Craig (Australian Journal of Agricultural and Resource Economics, 2024)
The quantity of ecosystem services produced from land cannot be readily measured at the site level needed for participation in ecosystem markets, or at a regional level needed to create ecosystem accounts. This paper applies biological scaling principles
Keywords: Biological Scaling; Ecosystem Accounts; Ecosystem Markets; Fractal Dimension; Ecosystem Services